Efektivitas Bimbingan Kelompok Dengan Teknik Bibliocounseling Untuk Meningkatkan Motivasi Belajar Siswa Kelas VIII Di SMP Negeri 4 Baubau - sri rezeky; Samsaifil (Frame (Jurnal Ilmiah Mahasiswa), 2024)
This study aims to examine group guidance with Bibliocounseling techniques to increase students' learning motivation. The main problem in this study is the effectiveness of group guidance services with Bibliocounseling techniques to increase student learning motivation in class VIII SMP Negeri 4 Baubau. The research method used Pre-Experimental with the form of One-Group Pretest-Postest Design: One-Group Pretest-Postest Design and used a quantitative approach. The population in this study was 24 students. The sampling technique used purposive sampling technique with a sample of 12 students. The data analysis technique in this study used the Wilcoxon test. This research resulted in: 1) General profile of Learning Motivation of Class VIII Students of SMP Negeri 4 Baubau: 2) Students' learning motivation has increased based on the wilcoxon test of 0.028 at a significant level of value <0.05 or (p<0.05),; 3) group guidance Bibliocounseling techniques proved effective for increasing student learning motivation.